Pleural FDG Uptake More Than a Decade after Talc Pleurodesis - Hilke Peek; Wouter van der Bruggen; Gijs Limonard (Case Reports in Medicine)
Talc pleurodesis induces a strong local inflammatory reaction which can be detected by PET scan for years after the procedure. When patients undergo PET scanning in the workup of a suspected malignancy later in life, pleural FDG uptake may unnecessarily lead to an additional invasive diagnostic workup. We present two cases of positive pleural PET findings more than 10 years after talc pleurodesis, where we adopted a watchful waiting approach. Positive pleural PET findings as a result of prior talc pleurodesis should always be included in the differential diagnosis of pleural abnormalities.